Sosialisasi Budidaya Perikanan Dalam Ember Sebagai Solusi Alternatif Pendapatan Masyarakat Di Desa Bolok, Kupang NTT - Yuli Valentine, Riris; Dian K, Ni Putu; Tangguda, Sartika; Hariyadi, Dimas Rizky (Jurnal Pengabdian Perikanan Indonesia, 2022)
Aquaculture is a food production sector that is developing quite rapidly in the world with a projection that production will double in the next 15-20 years. However, to run a cultivation system, you must have a large area of ​​land and large capital. The Covid-19 pandemic has had an impact on all aspects of people's lives. One of the aspects most affected by the pandemic is the economy, namely the occurrence of mass layoffs. Therefore, it is necessary to make alternative efforts that can help increase people's income during a pandemic, with a low risk of failure, and easy to implement as a side business during a pandemic. Budikdamber or also known as fish farming in buckets, can be an alternative business that can be done to maintain food security and increase income during a pandemic. Budikdamber is a form of fish farming that is inexpensive and easy to implement. The Budikdamber extension activity is one way to educate the community around Bolok Village, West Kupang, NTT. This PkM program was carried out with the output of the Budikdamber extension activity on November 9, 2020, attended by 56 participants from Bolok Village, West Kupang District, Kab. Kupang. The output of this program is that the people of Bolok Village are more educated about the easy and inexpensive practice of catfish farming in order to maintain independent food security in the midst of the Covid-19 pandemic and at the same time become an alternative solution for people's income, because they do not use large land and can take advantage of the yard. .